Experiences of probation officers working at Department of Social Development, Gauteng, JHB Metro Region on occupational stress and their coping mechanisms - Monnye, Olebogeng (University of the Witwatersrand, Johannesburg, 2022)
The United Nations Children’s Fund (UNICEF) states that the majority of children in conflict with the law have committed petty crimes such as alcohol abuse, begging, absenteeism from school and vagrancy. Probation officers have an important role to play in the lives of people in conflict with the law. Some of their responsibilities include conducting thorough investigations to assess the offenders who have committed crimes. It can be understood that the nature of their job can at times cause occupational stress. The aim of the study was to explore the occupational stressors and coping mechanisms adopted by probation officers working at the Department of Social Development (DSD), Johannesburg (Jhb) Metro Region in the Gauteng province of South Africa. A qualitative approach was used to conduct the study. Fifteen participants were selected using non-probability purposive sampling. Face to face in-depth interviews were conducted to collect the data. The interviews were audio recorded and the data was analysed using thematic analysis. It was anticipated that insights into the occupational stressors and coping strategies adopted by probation officers would be revealed. This study revealed that probation officers have high caseloads, but have good coping mechanisms to curb occupational stress in that they confide in their supervisors and their colleagues. The significance of the study for social work was that it may help probation officers to determine how they can better deal with occupational stress. Little research has been conducted in South Africa regarding probation officers’ occupational stressors. Therefore, this study contributed to literature on the matter.
A research report presented to the Department of Social Work, School of Human and Community Development: Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree Master of Arts in Social Work by Coursework and Research Report, 2022.
Keywords: Probation officer; Occupational stress; Coping mechanisms; Person environment theory; Lazarus and Folkman’s theory of stress; Department of Social Development; SDG-3: Good health and well-being